Mapping MAGE-A4 expression in solid cancers for targeted therapies - Habigt, Christin; Rottey, Sylvie; Spanggaard, Iben; Lopez, Juanita S.; Garralda, Elena; Calvo, Emiliano; Bechter, Oliver; Desai, Jayesh; Galot, Rachel; Gandhi, Leena; Heil, Florian; Rieder, Natascha; et al. (Frontiers in Oncology, 2025)
Melanoma-associated antigen A4 (MAGE-A4) is a promising target for anticancer therapy. However, limited contemporary data are available on the details of MAGE-A4 protein expression in different cancer types. In this study, the protein expression of MAGE-A4 is comprehensively studied in patients with unresectable and/or metastatic solid cancers to identify indications of the highest unmet medical need for anti-MAGE-A4 therapy. FFPE tumor sections from 200 patients, predominantly HLA-A*02:01 positive (n = 193), were examined using immunohistochemistry (IHC) to detect MAGE-A4 expression. The patient cohort comprised various cancer types to pinpoint differences in the prevalence and intensity of MAGE-A4 positivity. MAGE-A4 expression was observed in 35% (69 patients) of the overall cohort. Certain cancer types exhibited notably higher frequencies of MAGE-A4 positivity. Specifically, adenoid cystic carcinoma demonstrated the highest prevalence at 82%, followed by liposarcoma at 67%. Ovarian serous/high-grade carcinoma showed a 64% positivity rate, identical to that observed in squamous non-small cell lung cancer (NSCLC). Head and neck squamous cell carcinoma (HNSCC) presented a 60% prevalence, while esophageal cancer had a 54% prevalence of MAGE-A4 expression. These data highlight the variability of MAGE-A4 expression across different cancer types and underscore its relevance as a potential target of novel precision medicines. The significant presence of MAGE-A4 in specific cancers suggests potential for stratified therapeutic approaches and warrants further investigation into its role in oncogenesis and treatment response.